Evaluasi Penilaian Inspeksi Kesehatan Lingkungan Di Tiga Pasar Induk Kabupaten Lamongan - Cahyono, Ahmad; Putri, Marsha Savira Agatha; Sulistiono, Eko (VISIKES: Jurnal Kesehatan Masyarakat, 2023)
Environmental factors are important factors for healthy living, health efforts, control, and security of public facilities to prevent disease transmission. One of the public facilities is a market. In Lamongan Regency, there are three main markets that are the center of the community's economy, including: Sidoharjo Market, Sidomulyo Market, and Fish Market. Therefore it is necessary to evaluate the feasibility of environmental health. The type of research used is a mixture based on the results of observations and the results of the assessment listed in formular 2 (Permenkes) No. 17 of 2020 concerning Healthy Markets, to obtain the health feasibility of the market environment. From the results of these studies, it shows that the environmental health feasibility of the Sidoharjo market has not met the eligibility requirements for environmental health with a percentage (63.3%), the Sidomulyo market has not met the environmental health eligibility requirements with a percentage (55.7%), and for the fish market is not yet. meet the eligibility requirements for environmental health with a percentage (53.4%). Suggestions for the three markets to build hand washing facilities equipped with soap, plant trees around the market area for fresh air.Keywords: Evaluation, Environmental health, Market